2016
DOI: 10.1371/journal.pone.0155863
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Gut Microbiota of Native Tibetan and Han Populations Living at Different Altitudes

Abstract: The factors driving the composition of gut microbiota are still only partly understood but appear to include environmental, cultural, and genetic factors. In order to obtain more insight into the relative importance of these factors, we analyzed the microbiome composition in subjects of Tibetan or Han descent living at different altitudes. DNA was isolated from stool samples. Using polymerase chain reaction methodology, the 16S rRNA V1–V3 regions were amplified and the sequence information was analyzed by prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
98
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 39 publications
(33 reference statements)
12
98
1
Order By: Relevance
“…Our results are distinctly different from the observations in humans (Li & Zhao, ; Li, Gesang, et al. ), but are similar to the findings in pikas (Li et al., a). Despite observations in these different species are dissimilar, it is possible that the Firmicutes/Bacteroidetes (F/B) ratio is determined by the diet.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…Our results are distinctly different from the observations in humans (Li & Zhao, ; Li, Gesang, et al. ), but are similar to the findings in pikas (Li et al., a). Despite observations in these different species are dissimilar, it is possible that the Firmicutes/Bacteroidetes (F/B) ratio is determined by the diet.…”
Section: Discussioncontrasting
confidence: 78%
“…Comparative studies in pikas and humans living at different altitudes also confirmed that gut microbiota composition is influenced by altitude (Li & Zhao, 2015;Li, Gesang, et al 2016).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Anecdotal evidence of EPO affecting bacteria is present in the form of differences in gut microbiome of people who reside at high altitudes. Such populace has a high EPO level, which has been implicated as one of the reasons for altered microbiome [30]. However, it is too early to comment more specifically on the issue, and more focused studies must be done in the field.…”
Section: Discussionmentioning
confidence: 99%